Secondary-Source Core Reload Modeling with VERA. (4th March 2021) - Gentry, Cole; Collins, Benjamin; Davidson, Eva; Davidson, Gregory; Evans, Thomas; Godfrey, Andrew; Hart, Shane; Ilas, Germina; Johnson, Seth; Kim, Kang Seog; Palmtag, Scott; Pandya, Tara; et al.
Abstract: The CASL reactor simulation package VERA has been adapted to provide high-fidelity simulation capabilities for modeling source range detector response during subcritical reactor configurations. New features include the activation and shuffling of secondary-source assemblies, use of burned fuel neutron emission data from the ORIGEN depletion solver to the MPACT deterministic neutron transport solver, allowance of user-defined sources in MPACT based on material composition, ability to solve the subcritical source-driven system with neutron multiplication using the MPACT diffusion solver, and transfer of the calculated fission source from MPACT to the continuous-energy Monte Carlo solver Shift for final detector response evaluation using the CADIS methodology for variance reduction. These new capabilities were benchmarked against Watts Bar Unit 1 plant operating data for the first few fuel loading steps and were found to demonstrate excellent agreement with the measured data.